POSSIBILITIES FOR OPTIMIZATION OF DISTRIBUTIVE INDICES FOR AVERAGE COSTS CALCULATION IN JOB ORDER AND SMALL SCALE SERIAL PRODUCTION (Innovation in Woodworking Industry and Engineering design, 2026)
Calculation of total costs is often associated with distribution of costs like overhead which cannot be placed to one or another product costs at the end of planning period or just period of time. Furniture in Bulgaria consists mostly of small enterprises which produce individual customized products. In these cases, exist wide variety of approaches that could be implemented. In this paper is made an attempt to find an optimal solution of cost distribution mechanisms, suitable to furniture.